Touring Pacific cultures - Alexeyeff, Kalissa; Taylor, John Patrick (ANU Press, 2016)
'This collection is a welcome addition to tourism studies, or perhaps we should say post- or para-tourism. The essays bring out many facets and experiences too quickly bundled under a single label and focused exclusively on "destinations" visited by "outsiders". Tourism, we see here, actively involves many different populations, societies, and economies, a range of local/global/regional engagements that can be both destructive and creative. Western outsiders aren't the only ones on the move. Unequal power, (neo)colonial exploitation and capitalist commodification are very much part of the picture. But so are desire, adventure, pleasure, cultural reinvention and economic development. The effect, overall, is an attitude of alert, critical ambivalence with respect to a proliferating historical phenomenon. A bumpy and rewarding ride.' -- James Clifford, Professor Emeritus, University of California, Santa Cruz."